N002 A qualitative exploration into experiences of living with Crohn's anal fistula. (16th January 2018) - Adegbola, S; Dibley, L; Sahnan, K; Tozer, P; Yassin, N; Wade, T; Verjee, A; Sawyer, R; Mannick, S; Lung, P; Phillips, R; Faiz, O; et al.
Abstract: Background: Perianal fistulas affect about a third of patients with Crohn's disease (CD). Despite best medical and surgical treatment only a third of patients remain in remission at one year on maintenance treatment 1 and cure is often elusive. Apart from a small study of patients with CD-related and idiopathic anal fistulae, 2 there are little published data on patient perspectives of living with perianal Crohn's fistulas (pCF), or of coping strategies in the face of sometimes futile treatment. The aim of this study was to explore patients' experiences of living with pCF and impact on quality of life and routine functioning. Methods: As part of a study to develop a patient–reported outcome measure (PROM), we used an exploratory qualitative approach to capture patients' experiences of living with pCF via unstructured individual interviews ( n = 12). Participants with current/previous diagnosis of pCF were recruited from national IBD/bowel disease charities. Interviews took place either face to face in patients' homes, or via video-teleconferencing software, and were recorded digitally and professionally transcribed. Using a pragmatic thematic approach, data were analysed by team members (including patient advisors, clinicians and researchers) independently, before meeting to discuss and agree themes. Results: Experiences of Crohn's anal fistula were encompassed by several themes in three broad categories: (a) burden of symptoms; (b) burden of treatment; and (c) negative impact on emotional, physical, and social wellbeing (Figure 1). The experiences reveal burden and loss of opportunities, social activities, relationships and self-confidence, but also of hope, endurance and thriving in adversity. Pain and discharge are prominently present in patients' accounts, and clinical interventions such as insertion of bulky, inflexible setons are considered more problematic than beneficial. Consequently, patients may delay seeking treatment. Others can struggle to gain rapid access to knowledgeable clinicians at the start of a fistula flare. Conclusions: Patients' experiences of pCF are intense, often distressing, and debilitating; some can adapt their lives in positive ways. Interventions may be less helpful than clinicians expect, and for some patients, are worse than the condition itself, leading to treatment-avoidance behaviours. Better referral pathways for patients presenting to primary and secondary care services are required. The findings have also informed the development of a PROM for pCF. References: 1. Tozer PJ, et al . Long-term MRI-guided combined anti-TNF-α and thiopurine therapy for Crohn's perianal fistulas. Inflamm Bowel Dis, 2012. 2. Yassin N, et al. Living with anal fistulae. Gut, 2015;(Suppl. 1).